2021
DOI: 10.1186/s12905-021-01450-x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between women’s decision-making power over their own health care and use of modern contraception in the Democratic Republic of the Congo: a cross-sectional secondary data analysis

Abstract: Background In sub-Saharan Africa, the use of modern contraception (MC) is a critical intervention aimed at reducing mortality rates associated with unintended, high-risk pregnancies. However, among Congolese women aged 15–49, the prevalence of MC use is low. Research suggests that women’s general participation in decision-making is important in increasing MC use. However, little is known about the specific role of women’s decision-making power over their own health care and how it relates to MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…We also found that women who are involved in decisionmaking tend to be wealthier, or in a polygamous union. These expected demographic factors were significantly associated with women's involvement in decision-making and are seen in similar studies from across the sub-Saharan region [4,8,9,12,27]. In addition, women in our sample who were involved in household decision-making had listened to radio programming or had participated in their own marriage decision, compared to women who were not involved in decision-making.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…We also found that women who are involved in decisionmaking tend to be wealthier, or in a polygamous union. These expected demographic factors were significantly associated with women's involvement in decision-making and are seen in similar studies from across the sub-Saharan region [4,8,9,12,27]. In addition, women in our sample who were involved in household decision-making had listened to radio programming or had participated in their own marriage decision, compared to women who were not involved in decision-making.…”
Section: Discussionsupporting
confidence: 74%
“…Previous investigations of women’s decision-making as a predictor for a range of RH outcomes in diverse African contexts have found mixed effects. Research on modern family planning (FP) use found that women with greater wealth, educated partners, and decision-making power were more likely to have used contraceptives [ 4 ] and autonomous decision-making among women for their own health increased the odds of modern FP compared to women who were not involved in such decisions [ 8 ]. For instance, a study of 32 sub-Saharan African countries found that female adolescents who exhibit “reproductive health decision-making capacity”—as measured by self-reported ability to refuse sexual intercourse and ask partner to use a condom—had higher odds of using contraceptives and this increased with age, wealth, education, urban dwelling and if the adolescent was cohabitating and not married [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, 14.5 percent of women who used MC made health care decisions on their own, compared to 9.5 percent of those who did not. Finally, more over half of MC users decided on their partner's earnings together (56.4 percent) (23).…”
Section: Married Women Decision Making Power In Family Planning Utili...mentioning
confidence: 99%
“…As a result, though reproductive, maternal, neonatal, and child healthcare care in general and contraceptive method in particular are available, easily accessible, and mostly free of charge in Ethiopia as well (6, 25, 28, 37-40), uptake is not always ideal. Therefore, during the last seven years, the global and the national communities have shown a paradigm shift in ensuring the optimum use of contraceptive services (41). This is shown by the fact that goal 5.6.1 of the women's empowerment main agenda lists the right of women to make decisions about contraceptive as a top SDG sub-agenda (8, 9, 24, 42) In Ethiopia, contraceptive method decision making received minimal or no attention likewise.…”
Section: Introductionmentioning
confidence: 99%